Dificultades de acceso a los créditos en la Mypes en la ciudad de Iquitos - Macahuachi Orbe, Henry Guido (2020)
The objective of this research is to determine the main difficulties Mypes have in accessing a loan in the city of Iquitos. It was surveyed by micro and small companies dedicated to wholesale and retail trade from which, it has been observed that they have requested a financial credit and indeed they have complied with all the requirements and standards requested by banks, however, the risk analysts have taken into account other aspects that gave rise to the rejection and that will be explained throughout the research carried out. In the same way, the results of the research are shown through a series of graphs and tables based on the surveys carried out, where the reasons for which the banks reject the credits requested by the Mypes are exposed, for this reason they will provide them with the necessary information so that they comply with all the requirements established by each banking entity and that they will benefit from access to a credit for any purpose that businessmen require.